Răspuns :
Răspuns:
Explicație pas cu pas:
a)
E(x) = [ 3 x / (x + 1 ) - 1 ] : [ 1 + 3 x² / (x² - 1) ]
E(x) = [(3 x - x - 1) / ( x + 1)] : [ ( x² - 1 + 3 x² ) / ( x² - 1 ) ]
E(x) = [ ( 2 x - 1 ) / ( x + 1 ) ] : [ ( 4 x² - 1 ) / ( x² - 1 ) ]
E(x) = [ ( 2 x - 1 ) / ( x + 1 ) ] × [ ( x² - 1 ) / ( 4 x² - 1) ]
E( x) = [ ( 2 x - 1 ) / ( x + 1 ) ] × [ ( x + 1) ( x + 1 ) / ( 2 x - 1 ) ( 2 x + 1 ) ]
E( x ) = ( x - 1 ) / ( 2 x + 1 ) √
_________________________________________
b)
2 × E( x ) - 7 = 0
2 × ( x - 1 ) / ( 2 x + 1 ) = 7
7 ( 2 x + 1 ) = 2 ( x - 1 )
14 x + 7 = 2 x - 2
14 x - 2 x = - 2 - 7
12 x = - 9
x = - 9 / 12
x = - 3 / 4
Răspuns:
n.c x-1 si x²-1 ; (3X-X-1)\(X+1):(X²-1+3X²)(X²-1)=(2X-1)\(X+1)×(X+1)(X-1)\(2X+1)(2X-1)=(X-1)\(2X+1) ; b) (2x-2)\(2x+1)-7=0 ; se amplifica cu2x+1 ; 2x-2-7(2x+1)=0 ; 2x-2-7x-7=0 ; -5x=9 ; x=-9\5
Explicație pas cu pas: